2014
DOI: 10.1016/j.ypmed.2013.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Weight gain prevention in the school worksite setting: Results of a multi-level cluster randomized trial

Abstract: Objective To describe the effectiveness, reach and implementation of a weight gain prevention intervention among public school employees. Method A multi-level intervention was tested in a cluster randomized trial among 782 employees in 12 central Massachusetts public high schools from 2009 to 2012. The intervention targeted the nutrition and physical activity environment and policies, the social environment and individual knowledge, attitudes and skills. The intervention was compared to a materials only cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(73 citation statements)
references
References 25 publications
(30 reference statements)
1
71
0
1
Order By: Relevance
“…While the modest weight change observed in the current study is not clinically significant, small shifts in population weight may result in large population benefit . The worksite‐based intervention specifically targeted worksite support ; thus, increases in perceived coworker support for physical activity were seen among intervention participants over time as hypothesized, with no significant changes in family, friend, or coworker support observed for the overall study sample. These findings suggest that strategies to help individuals: 1) solicit support (either from existing members of their social network and/or from new members) among those reporting low support for healthy eating and physical activity; and 2) navigate social undermining of healthy eating and physical activity among those reporting frequent social undermining may be key intervention targets for clinicians, practitioners, and investigators.…”
Section: Discussionmentioning
confidence: 56%
“…While the modest weight change observed in the current study is not clinically significant, small shifts in population weight may result in large population benefit . The worksite‐based intervention specifically targeted worksite support ; thus, increases in perceived coworker support for physical activity were seen among intervention participants over time as hypothesized, with no significant changes in family, friend, or coworker support observed for the overall study sample. These findings suggest that strategies to help individuals: 1) solicit support (either from existing members of their social network and/or from new members) among those reporting low support for healthy eating and physical activity; and 2) navigate social undermining of healthy eating and physical activity among those reporting frequent social undermining may be key intervention targets for clinicians, practitioners, and investigators.…”
Section: Discussionmentioning
confidence: 56%
“…The length of the interventions ranged from six weeks to two years. Nine studies had outcome assessments at follow-up times ranging from six months to 3 years (Fulkerson et al, 2015; Hesselink et al, 2015; Kokkvoll, Grimsgaard, Steinsbekk, Flaegstad, & Njolstad, 2015; Lemon et al, 2014; ter Bogt et al, 2011; Valve et al, 2013; Vermunt et al, 2012; Wilson et al, 2016; Wright et al, 2013). Furthermore, nine studies reported nurses delivering interventions within multidisciplinary teams (Andryukhin, Frolova, Vaes, & Degryse, 2010; Brown et al, 2011; Brown, Goetz, Hamera, & Gajewski, 2014; Fulkerson et al, 2015; Gallagher et al, 2012; Kokkvoll et al, 2015; Lemon et al, 2014; Vermunt et al, 2012; Wilson et al, 2016; Wright et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 782 participants enrolled, 80.6% completed follow‐up through 24 months (n = 630). Additional details regarding intervention conditions, recruitment, and retention procedures have been previously described …”
Section: Methodsmentioning
confidence: 99%
“…This study sought to address this research gap by assessing the impact of school employees' health risk factors on their work productivity and absenteeism, analyzing data from a school employee weight maintenance intervention in 12 secondary schools in central Massachusetts . Specifically, this study examined 3 common health risk factors—obesity, depressive symptoms, and smoking—that have been shown to impact employee productivity and are potentially modifiable/treatable.…”
mentioning
confidence: 99%
See 1 more Smart Citation